THE INFLUENCE OF TEACHERS’ PROFESSIONAL COMPETENCE AND TEACHING EXPERIENCE ON STUDENTS’ LEARNING ABILITY AT SMA NEGERI 1 MOTOLING - Alexsandro Nusi; Johny Tarore; Amsje Winokan (Program Studi Pendidikan Bahasa Inggris, 2025)
This study aims to examine the influence of teachers’ professional competence and teaching experience on students’ learning ability at SMA Negeri 1 Motoling. The population of the study comprises all 95 students of SMA Negeri 1 Motoling, while the sample used consists of 77 students, selected through simple random sampling to ensure data representativeness. Data were collected using questionnaires and observations, then analyzed using simple and multiple regression techniques. The results indicate that teachers’ professional competence has a positive and significant effect on students’ learning ability, meaning that teachers with higher mastery of subject matter, pedagogical skills, and classroom management can enhance student learning outcomes. Similarly, teachers’ teaching experience positively and significantly affects students’ learning ability, where more experienced teachers are able to manage learning more effectively and adapt teaching strategies to students’ needs. Furthermore, the combination of professional competence and teaching experience simultaneously contributes significantly to students’ learning ability, explaining approximately 54.7% of the variance in learning outcomes. These findings emphasize the importance of developing teachers’ professional competence and teaching experience simultaneously to improve students’ learning ability. Schools are recommended to provide professional development programs, mentoring, and training for teachers to strengthen their competence and practical experience, thereby enhancing the effectiveness of the teaching and learning process and improving student academic achievement.